An Analysis of Politeness Maxims in the Movie “The Adventure of Tintin” - I Made Dwi Nova Muliartha; Ida Ayu Putri Gita Ardiantari (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study explored the types of politeness maxims that the main characters utilized and investigated the factors that influenced their use. The data were collected through focusing on observing main character specially